Epoxy resin composition, surface protective intermediate base and fiber-reinforced composite material intermediate

JP2022153282A5Active Publication Date: 2025-02-25TORAY INDUSTRIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022027462
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2022-02-25
Publication Date
2025-02-25
Estimated Expiration
2042-02-25

AI Technical Summary

Technical Problem

Existing epoxy resin compositions used in fiber-reinforced composite materials lack sufficient UV resistance, leading to degradation when exposed to light, and they also face issues with resin flow control during curing, resulting in uneven surfaces and poor adhesion.

Method used

A non-aromatic epoxy resin composition containing specific components such as non-aromatic epoxy resins, pigments, non-aromatic thermoplastic resins, non-aromatic acid anhydrides, curing accelerators, and thixotropic agents, which are formulated to provide high UV resistance, controlled resin flow, and improved adhesion.

Benefits of technology

The composition achieves excellent UV resistance, controlled resin flow, and enhanced adhesion, preventing surface degradation and ensuring uniform application and curing of fiber-reinforced composite materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a surface protective material capable of protecting a prepreg surface that is rich in UV resistance and becomes a host material, capable of preventing inconvenience during coating by preventing deterioration due to UV of a fiber-reinforced composite material, capable of controlling a resin flow, and less in a volatilization amount during curing.SOLUTION: An epoxy resin composition contains constituent elements [A] to [F] in the following amounts with respect to 100 pts.mass of a total epoxy resin. [A] 90 to 100 pts.mass of non-aromatic epoxy resin, [B] 0.05 to 75 pts.mass of pigment having an average particle size of 0.1 to 10 μm, [C] 0.05 to 100 pts.mass of non-aromatic thermoplastic resin, [D] 50 to 200 pts.mass of non-aromatic acid anhydride, [E] 0.1 to 10 pts.mass of a curing accelerator, and [F] 0.1 to 20 pts.mass of a thixotropy imparting agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an epoxy resin composition having excellent light resistance for use as a coating agent for fiber-reinforced composite materials, a resin film, and a surface-protecting intermediate substrate. [Background technology]

[0002] Prepregs, which are made by impregnating reinforcing fibers such as carbon fiber with thermosetting resins such as epoxy resin, are often used in products that require high structural performance, such as aircraft structural components, wind turbine blades, automobile exterior panels, and computer applications such as IC trays and laptop computer housings. However, fiber composite materials obtained by curing typical prepregs have poor light resistance (UV resistance), and their surfaces deteriorate and degrade when exposed to light. Therefore, in recent years, there has been an increasing demand for fiber composite material surfaces that can be made light resistant.

[0003] Patent Document 1 discloses a sheet material with UV blocking properties as a surface protection film for fiber-reinforced composite materials. Patent Document 2 also discloses a UV-resistant resin composition that combines an epoxy resin that does not contain an aromatic ring with a carboxylic acid anhydride that also does not contain an aromatic ring and an ultraviolet absorber. Non-aromatic epoxy resins generally have low molecular weights and weak intermolecular interactions, resulting in low viscosity and easy volatility. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2015-507648 [Patent Document 2] International Publication No. 2003 / 002661 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the technology disclosed in Patent Document 1 has the problem that the epoxy resin composition used as the film material contains an aromatic ring, and the film material itself has poor UV resistance. Furthermore, the technology disclosed in Patent Document 2 uses a carboxylic acid anhydride as a curing agent for the epoxy resin composition, but has unresolved problems such as difficulty in handling the surface protection material and difficulty in controlling the resin flow. Furthermore, since the UV-resistant resin composition disclosed in Patent Document 2 does not allow for easy control of the resin flow, when a surface protection material obtained using the resin composition is applied to the surface of an uncured fiber-reinforced composite material precursor and cured, the non-UV-resistant resin contained in the precursor may mix with the surface protection material during the curing process, resulting in the non-UV-resistant resin being exposed on the surface of the resulting fiber-reinforced composite material, which is problematic in that it is not possible to impart sufficient UV resistance.

[0006] Therefore, the challenge is to develop a surface protection material that is highly UV resistant, can protect the surface of the prepreg base material, can prevent UV degradation of fiber-reinforced composite materials and prevent defects during painting, and can also control the resin flow and emit little vapor during curing. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention has the following configuration: That is, the epoxy resin composition of the present invention contains at least the components [A] to [F] in the following amounts, respectively, per 100 parts by mass of the total epoxy resin: [A] Non-aromatic epoxy resin 90 to 100 parts by mass [B] 0.05 to 75 parts by mass of pigment with an average particle size of 0.1 to 10 μm [C] Non-aromatic thermoplastic resin 0.05~100 parts by mass [D] Non-aromatic acid anhydride 50-200 parts by mass [E] Curing accelerator 0.1 to 10 parts by mass [F] Thixotropy imparting agent 0.1 to 20 parts by mass The surface protective intermediate substrate of the present invention is the above-mentioned epoxy resin composition integrated with a support, and examples of the support include reinforcing fiber, metal mesh, or metal foil, and may also be a film of a thermoplastic resin, etc. On the other hand, the resin film of the present invention is a material obtained by forming the epoxy resin composition into a sheet, and includes a material integrated with release paper, but is different from the surface protective intermediate substrate of the present invention.

[0008] Furthermore, the fiber-reinforced composite material intermediate of the present invention is obtained by disposing the above-mentioned epoxy resin composition or a surface-protecting intermediate base material on the surface of a fiber-reinforced composite material precursor (described later), and by molding it, a fiber-reinforced composite material can be obtained. [Effects of the Invention]

[0009] The present invention can provide an epoxy resin composition having excellent light resistance for use as a coating agent for fiber-reinforced composite materials, a resin film, or a surface-protecting intermediate substrate, as well as a coating agent, a resin film, or a surface-protecting intermediate substrate using the composition. DETAILED DESCRIPTION OF THE INVENTION

[0010] Component [A] of the present invention is a non-aromatic epoxy resin. Here, "aromatic" refers to compounds that contain aromatic hydrocarbons or conjugated unsaturated heterocyclic compounds in their chemical structure, while anything else is "non-aromatic." Non-aromatic compounds have a non-cyclic or non-planar molecular structure, and do not have a conjugated π system within the ring. Examples of non-aromatic compounds include saturated aliphatic hydrocarbons, cyclohexane, and cyclohexene. Therefore, examples of non-aromatic epoxy resins include alicyclic epoxy resins (epoxy resins containing a cycloalkane ring), such as tetrahydroindene diepoxide, vinylcyclohexene oxide, (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexanecarboxylate, dipentene dioxide, bis(3,4-epoxycyclohexylmethyl) adipate, dicyclopentadiene dioxide, bis(2,3-epoxycyclopentyl)ether, and 1,2-epoxy of 2,2-bis(hydroxymethyl)-1-butanol. Oxy-4-(2-oxiranyl)cyclohexane adduct, epoxidized butanetetracarboxylic acid tetrakis-(3-cyclohexenylmethyl) modified epsilon-caprolactone, bi-7-oxabicyclo[4.1.0]heptane, dodecahydrobisphenol A diglycidyl ether, dodecahydrobisphenol F diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, hexahydrophthalic acid diglycidyl ester, hexahydroterephthalic acid diglycidyl ester, 2,2-bis(4-hydroxycyclohexane Specific examples of epoxy resins that do not contain any of the following: diglycidyl ether of bisphenol A-hydroxypropane (generic name: hydrogenated bisphenol A liquid epoxy resin); aromatic rings, amine nitrogen atoms, cycloalkane rings, and cycloalkene rings include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,6-hexanediol diglycidyl ether, neopentylene glycol diglycidyl ether, glycerol polyglycidyl ether, and diglycerol polyglycidyl ether. , trimethylolpropane polyglycidyl ether, sorbitol polyglycidyl ether, 1,4-bis(2-oxiranyl)butane, pentaerythritol polyglycidyl ether, and specific examples of monofunctional epoxy compounds (epoxy compounds containing only one oxirane ring) that do not contain any aromatic ring or amine nitrogen atom include 4-tert-butyl glycidyl ether, butyl glycidyl ether, 1-butene oxide, 1,2-epoxy-4-vinylcyclohexane, and 2-ethylhexyl glycidyl ether.

[0011] From the viewpoint of heat resistance, alicyclic epoxy resins are preferably used as the non-aromatic epoxy resins.

[0012] The non-aromatic epoxy resin may be a commercially available product. Examples include (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexanecarboxylate under the trade name "Celloxide (registered trademark)" 2021P (manufactured by Daicel Chemical Industries, Ltd.), epoxidized butanetetracarboxylic acid tetrakis-(3-cyclohexenylmethyl)-modified epsilon-caprolactone under the trade name "Epolead (registered trademark)" GT401 (manufactured by Daicel Chemical Industries, Ltd.), 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol under the trade name "EHPE3150" (manufactured by Daicel Chemical Industries, Ltd.), and diglycidyl ethers of 2,2-bis(4-hydroxycyclohexyl)propane under the trade name "ST-3000" (manufactured by Nippon Steel Chemical & Material Co., Ltd.), "YX8000" (manufactured by Mitsubishi Chemical Corporation), and "EPALOY5000" (manufactured by Huntsman).

[0013] The use of at least two types of the non-aromatic epoxy resins is preferred because it allows the reactivity of the epoxy resin composition to be controlled and a good balance between the low-temperature curing property and the pot life of the epoxy resin composition to be obtained.

[0014] The epoxy resin composition of the present invention can achieve high light resistance (UV resistance) by containing the non-aromatic epoxy resin in an amount of 90 mass % or more based on the total amount of epoxy resins.

[0015] Furthermore, when only an alicyclic epoxy resin is used in the epoxy resin composition, it is possible to obtain a cured epoxy resin product that has UV resistance and a high glass transition temperature.

[0016] Component [B] is a pigment (average particle size 0.1 to 10 μm). Examples of pigments include barium sulfate, zinc sulfide, titanium oxide, molybdenum red, cadmium red, chromium oxide, titanium yellow, cobalt green, cobalt blue, ultramarine, barium titanate, carbon black, iron oxide, red phosphorus, and copper chromate. The average particle size of the pigment must be 0.1 to 10 μm, preferably 0.1 to 5 μm, and more preferably 0.3 to 5 μm, to obtain an epoxy resin composition with high UV blocking properties. Here, the average particle size is measured using a laser diffraction scattering method (e.g., preferably an LA-950 (manufactured by Horiba, Ltd.)). The volumetric results measured using "Araldite (registered trademark)" GY282 (component: bisphenol F-type epoxy resin, manufactured by Huntsman Japan Co., Ltd.) as the dispersion medium during measurement are used as the particle size distribution measurement results, and the particle size (median diameter) at 50% of the cumulative curve of the obtained particle size distribution is taken as the average particle size. The preferred range of the average particle size may be any combination of the upper and lower limits described above. The same applies to the various numerical ranges described hereinafter in this specification.

[0017] By including the pigment in an amount of 15 to 75 parts by mass, preferably 25 to 55 parts by mass, and more preferably 30 to 50 parts by mass relative to 100 parts by mass of the total epoxy resin contained in the epoxy resin composition, it is possible to obtain a good balance between the light-shielding properties of the cured resin product and the adhesion when applied by hand or when attached to a target surface with a resin film or a surface-protecting intermediate substrate.

[0018] Component [C] is a non-aromatic thermoplastic resin, and is contained in an amount of 0.05 to 100 parts by mass, preferably 0.05 to 30 parts by mass, per 100 parts by mass of the total epoxy resin. Examples of non-aromatic thermoplastic resins include polyvinyl alcohol, polyvinyl acetal, polyvinyl formal, polyvinyl acetoacetal, polyvinyl butyral, polyvinyl acetate, hydrogenated bisphenol A-pentaerythritol phosphite polymer, hydrogenated terpene, and hydrogenated terpene phenol.

[0019] In particular, polyvinyl alcohol, polyvinyl formal, polyvinyl butyral, polyvinyl acetoacetal, and polyvinyl vinyl acetate, which have high solubility in non-aromatic epoxy resins, are preferred because they allow for easy viscosity adjustment of the epoxy resin composition. Polyvinyl acetoacetal and polyvinyl butyral are even more preferred because they improve the elongation of the cured epoxy resin composition. Here, elongation refers to the bending strain (%) when the cured epoxy resin composition is bent at three points in a predetermined shape.

[0020] These non-aromatic thermoplastic resins are preferably soluble in the epoxy resin of component [A]. In the present invention, at least 10 parts by mass of thermoplastic resin powder is added to 100 parts by mass of the epoxy resin of component [A], and the mixture is kneaded at 100 to 120°C for 1 hour. A thermoplastic resin that exhibits a weight loss from the initial weight loss is considered soluble. Weight loss refers to a powder that is so small that it is optically unobservable, or a powder that exhibits a weight loss of 10% or more from the initial weight loss when the remaining powder is recovered. From the perspective of dissolving the thermoplastic resin in the epoxy resin, it is preferable that the thermoplastic resin powder have an average particle size of at least 100 μm as determined by laser diffraction. Furthermore, an average particle size of more than 100 nm is preferable because it prevents aggregation during storage and facilitates mixing with the epoxy resin.

[0021] Furthermore, when the molecular weight of these non-aromatic thermoplastic resins is 5,000 to 70,000 g / mol, preferably 7,000 to 65,000 g / mol, and more preferably 10,000 to 60,000 g / mol, a good balance can be achieved between the uniformity of dissolution in the epoxy resin composition and the resin flow suppression effect. Here, the molecular weight refers to the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (for example, HLC-8420GPC (manufactured by Tosoh Corporation)).

[0022] The non-aromatic thermoplastic resin may be commercially available. Examples include polyvinyl alcohol (J-POVAL®, manufactured by Nippon Vinyl Acetate & Poval Co., Ltd.), polyvinyl formal (Vinyllec® K, Vinyllec® H, and Vinyllec® L), polyvinyl acetoacetal (S-LEC® KS-10, manufactured by Sekisui Chemical Co., Ltd.), and polyvinyl butyral (S-LEC® BX-L, Sekisui Chemical Co., Ltd.), S-LEC® BM-5, and S-LEC® BH-3(Z), manufactured by Sekisui Chemical Co., Ltd.

[0023] When applying an epoxy resin composition as a spray, the resin flow suppression effect can be achieved by including 0.05 parts by mass or more of the non-aromatic thermoplastic resin per 100 parts by mass of the total epoxy resins contained in the epoxy resin composition. Here, "spraying" refers to a method in which the epoxy resin composition is filled into a container and sprayed into a mist or foam using a nozzle with high-pressure air or mechanical movement. When applying an epoxy resin composition as a spray, including 0.05 to 1 part by mass, preferably 0.1 to 0.5 parts by mass of the non-aromatic thermoplastic resin, is preferred because it maintains a high spray volume per unit time and achieves a high resin flow suppression effect. This effect prevents the precursor's constituent resins from mixing with the coating agent during the molding process, resulting in the exposure of non-UV-resistant resins to the surface, when the coating agent comprising the epoxy resin composition of the present invention is applied to the surface of a precursor of a fiber-reinforced composite material (described below) to be surface-protected to obtain an intermediate, which is then molded and cured together. (Hereinafter, the effect of suppressing the mixing of the precursor's constituent resins during the molding process, not limited to the case of a coating agent, is referred to as the "resin mixing suppression effect.")

[0024] When applying an epoxy resin composition by hand, the non-aromatic thermoplastic resin is present in an amount of 1 to 30 parts by mass or less, preferably 5 to 25 parts by mass, and more preferably 10 to 20 parts by mass, per 100 parts by mass of the total epoxy resin, thereby achieving a good balance between the effect of suppressing resin flow during molding, the effect of suppressing resin mixing, and adhesion properties and ease of handling. Hand application here refers to, for example, a method in which the epoxy resin composition is stored in a container, a brush or roller is dipped into the epoxy resin composition, and then the composition is applied to the target by hand with the brush or roller, or a method in which the epoxy resin composition is placed on the target and then spread using a spatula or bar coater.

[0025] Furthermore, when the epoxy resin composition is used as a film (resin film), the non-aromatic thermoplastic resin is contained in an amount of 30 to 100 parts by mass, preferably 40 to 90 parts by mass, and more preferably 50 to 80 parts by mass per 100 parts by mass of the total epoxy resin, thereby achieving a good balance between the effect of suppressing resin flow during molding, the effect of suppressing resin mixing as described above, and adhesion properties and handleability. Because the resin film is easy to handle, it can also be used as a surface protection intermediate substrate by impregnating it into a support such as a thermoplastic resin film, a fiber substrate, a metal foil, or a metal mesh.

[0026] Component [D] is a non-aromatic acid anhydride. Examples of non-aromatic acid anhydrides include hexahydrophthalic anhydride, tetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, and bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride.

[0027] The non-aromatic acid anhydride may be a commercially available product. Examples include hexahydrophthalic anhydride "RIKACID (registered trademark)" HH (manufactured by Shin-Nippon Rikagaku Co., Ltd.), tetrahydrophthalic anhydride "RIKACID (registered trademark)" TH (manufactured by Shin-Nippon Rikagaku Co., Ltd.), and a mixture of methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride and bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride "RIKACID (registered trademark)" NHA-100 (manufactured by Shin-Nippon Rikagaku Co., Ltd.).

[0028] The use of at least two types of the non-aromatic acid anhydrides is preferred because it allows the reactivity of the epoxy resin composition to be controlled and a good balance between the low-temperature curing properties and pot life of the epoxy resin composition to be obtained.

[0029] The non-aromatic acid anhydride is contained in an amount of 50 to 200 parts by mass, preferably 100 to 150 parts by mass, and more preferably 100 to 140 parts by mass, relative to 100 parts by mass of the total epoxy resin contained in the epoxy resin composition of the present invention, thereby exhibiting low-temperature curing properties, and thereby achieving an effect of suppressing resin flow and volatilization during molding, and a good balance of low-temperature curing properties, pot life, and UV resistance.

[0030] Furthermore, the epoxy resin composition of the present invention contains a curing accelerator as a component [E]. Examples of curing accelerators include imidazole compounds and their derivatives, and triphenylphosphine and its derivatives. By appropriately selecting the type and amount of non-aromatic acid anhydride and curing accelerator, the reactivity of the coating agent comprising the epoxy resin composition can be controlled. Specifically, increasing the amount of addition imparts the effect of initiating the reaction at a low temperature, thereby suppressing the mixing of the resins.

[0031] As described above, the present invention is advantageous in that, during the process of applying or attaching a coating agent, resin film, or surface-protecting intermediate substrate made of an epoxy resin composition to a fiber-reinforced composite material precursor such as a prepreg, the epoxy resin composition has a fast curing rate, which makes it easier to cure than the resin of the fiber-reinforced composite material precursor. This effectively suppresses the amount of resin contamination, thereby reducing the likelihood of the precursor resin being mixed into the epoxy resin composition during curing, and also suppresses volatilization of the epoxy resin composition. Here, the DSC exothermic peak temperature of the epoxy resin composition depends on the curing temperature of the fiber-reinforced composite material precursor, but is preferably at least 40°C lower, more preferably at least 60°C lower, than the curing temperature of the resin of the fiber-reinforced composite material precursor. When the curing temperature of the resin of the fiber-reinforced composite material precursor is 180°C, it is also preferable from the standpoint of ease of handling if the DSC exothermic peak temperature of the epoxy resin composition is in the range of 80 to 120°C.

[0032] The epoxy resin composition of the present invention also contains a thixotropy-imparting agent as component [F]. Examples of the thixotropy-imparting agent include silicon dioxide, magnesium silicon sodium fluoride hydroxide oxide, alkyl quaternary ammonium salt, synthetic hectorite, clay minerals, modified bentonite, and mixtures of minerals and organically modified bentonite.

[0033] The thixotropy-imparting agent may be a commercially available product, and examples thereof include silicon dioxide (fumed silica) such as "Aerosil (registered trademark)" (manufactured by Nippon Aerosil Co., Ltd.), and alkyl quaternary ammonium salts such as "GARAMITE (registered trademark)" 1958 and "LAPONITE (registered trademark)" (manufactured by BYK Corporation).

[0034] By including the thixotropy-imparting agent in an amount of preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the total epoxy resin contained in the epoxy resin composition of the present invention, it is possible to obtain a good balance between the effect of suppressing resin flow during molding, the accompanying effect of suppressing the mixing of the resins described above, and adhesion properties and handleability.

[0035] The epoxy resin composition of the present invention may contain rubber as component [G]. Examples of rubber include natural rubber, diene rubber, and non-diene rubber. Examples of diene rubber include styrene-butadiene rubber, isoprene rubber, butadiene rubber, chloroprene rubber, and acrylonitrile-butadiene rubber. Examples of non-diene rubber include butyl rubber, ethylene-propylene rubber, ethylene-propylene-diene rubber, urethane rubber, silicone rubber, and fluororubber.

[0036] Of the above, non-diene rubbers are preferred, and ethylene-propylene rubber, ethylene-propylene-diene rubber, silicone rubber, and fluororubber, which do not have double bonds in the polymer backbone, are particularly preferred because they have high light resistance and have little effect on the UV resistance of the epoxy resin composition of the present invention. Furthermore, powder-like rubber is particularly preferred because it has excellent dispersibility in the epoxy resin composition. The inclusion of rubber in the epoxy resin composition inhibits resin flow and improves the elongation of the epoxy resin composition after curing, thereby preventing cracking after painting.

[0037] The rubber may be a commercially available product, and examples thereof include silicone rubbers such as KMP-598, KMP-600, KMP-601, KMP-602, and KMP-605 (manufactured by Shin-Etsu Chemical Co., Ltd.), and acrylonitrile-butadiene polymers such as JSR PN30A (manufactured by JSR Corporation).

[0038] The epoxy resin composition according to the present invention may consist of the above [A] to [F], or may consist of [A] to [G] including the above [G]. However, additives may be added as long as they do not impair the effects of the invention.

[0039] From the viewpoints of the working environment and accurate control of thickness after molding, it is preferable that the spray or hand-applied coating agent, resin film, and surface protection intermediate substrate made from the epoxy resin composition of the present invention have an volatilization amount of 10% or less after being left in an environment of 180°C for 1 hour.

[0040] The epoxy resin composition of the present invention is cured by irradiating the cured product with UV light having a wavelength of 300 to 400 nm at a rate of 1000 kJ / m 2 It is preferable that no discoloration occurs after irradiation from the viewpoint of UV resistance, and the coated object can be protected from UV. In the present invention, no discoloration occurs under such conditions because the difference in color ΔE * Since ab is less than 4, the formula difference ΔE * ab can be determined by measuring the colorimetric values ​​of the cured product of the epoxy resin composition before and after irradiation under the above conditions using a multi-light source spectrocolorimeter.

[0041] The epoxy resin composition of the present invention can be applied to a metal surface for spray application or hand application, and the resin film and surface-protecting intermediate substrate can be cured by heat after application to the metal surface. Alternatively, the composition can be applied or attached (also referred to as a "fiber-reinforced composite intermediate" in the present invention) to the outermost surface of uncured prepregs, resin transfer molding (RTM) materials, and resin film infusion (RFI) materials commonly used in fiber-reinforced composites (collectively referred to as "fiber-reinforced composite precursors" in the present invention) and then cured by heat in that state. Here, prepregs are fiber-reinforced composite precursors obtained by impregnating reinforcing fibers with a thermosetting resin such as an epoxy resin. RTM materials are fiber-reinforced composite precursors obtained by stacking reinforcing fiber substrates in a mold and injecting a liquid thermosetting resin into the reinforcing fiber substrate. RFI materials are fiber-reinforced composite precursors obtained by overlaying a thermosetting resin film on a reinforcing fiber substrate, laminating them, and then impregnating the reinforcing fiber substrate with the thermosetting resin by heating and pressurizing. When applying to a metal surface, a silane coupling agent may be applied to the metal surface before application, and the metal surface may then be treated with a light source or heat before applying the epoxy resin composition. By treating with the silane coupling agent, the silane coupling agent acts as a bridge between the metal surface and the coating agent of the epoxy resin composition of the present invention, thereby improving the adhesion between the metal surface and the coating agent and improving the wettability of the coating agent to the metal surface. Upon curing, the cured product of the epoxy resin composition of the present invention covers the surface of the cured fiber-reinforced composite material precursor, thereby obtaining an integrated fiber-reinforced composite material.

[0042] As the reinforcing fibers in the fiber-reinforced composite material precursor, various carbon fibers, graphite fibers, glass fibers, aramid fibers, etc. are preferably used.

[0043] The spray or hand-applied coating agent comprising the epoxy resin composition of the present invention exerts its effect by being applied to a fiber-reinforced composite material precursor and then thermally cured together, but the epoxy resin composition can be applied to an object by various methods, such as by spraying as described above, or by hand application using a brush or a bar coater, etc. Furthermore, after hand application, it is also possible to enhance adhesion between the coating agent and the fiber-reinforced composite material precursor by using a release film or the like and evacuating.

[0044] In either method, the epoxy resin composition may be applied while being heated as needed to lower its viscosity.

[0045] As described above, the spray or hand-applied coating agent comprising the epoxy resin composition of the present invention can be applied to a target object using a variety of methods. The preferred application method depends on the viscosity of the epoxy resin composition at 70°C, with a preferred range being 0.01 to 30 Pa·s. A viscosity at 70°C of 0.01 to 0.1 Pa·s is preferred because it facilitates application by spraying. When applying by spraying, a viscosity at 70°C of 0.01 Pa·s or higher can suppress resin flow at room temperature and maintain a uniform coating thickness, while a viscosity at 70°C of 0.1 Pa·s or lower can prevent clogging of the epoxy resin composition during spraying, improving workability.

[0046] When the viscosity of the epoxy resin composition at 70°C is 0.1 to 30 Pa·s, hand application using a roller, brush, bar coder, or the like is preferred. If the viscosity of the epoxy resin composition at 70°C is 0.1 Pa·s or higher, sagging during application can be suppressed, which is preferable, and if it is 30 Pa·s or lower, a brush or roll can be easily immersed in the epoxy resin composition, resulting in good workability. The method for measuring the viscosity mentioned above will be described later.

[0047] When the spray or hand-applied coating agent comprising the epoxy resin composition of the present invention is applied to a fiber-reinforced composite material precursor, the basis weight of the epoxy resin composition is 30 to 300 g / m 2It is preferable that the weight of the epoxy resin composition is 30 g / m 2 When the epoxy resin composition has a basis weight of 300 g / m or more, the surface of the fiber-reinforced composite material can be covered without being visible through the surface, and sufficient light resistance can be exhibited. 2 If the content is not more than this, heat generation during curing of the epoxy resin composition can be suppressed when molding it together with a fiber-reinforced composite material, which is preferable.

[0048] The epoxy resin composition according to the present invention is formed into a resin film, for example, by coating it on a release sheet and forming it into a sheet, and the resin film with the release sheet is pre-cured by light or heat (in the present invention, a material in which the epoxy resin composition is coated on a release sheet is referred to as a "resin film with a release sheet," and the sheet-like epoxy resin composition alone is referred to as a "resin film"). Here, the release sheet is a material that makes it easy to release the resin film after curing, and examples include release paper and release film. The release sheet is preferably paper (release paper) from the viewpoints of strength and ease of handling.

[0049] The thermosetting resin composition is coated onto a release sheet using the hot melt method. Resin films produced using the hot melt method are preferable because they leave no residual solvent and are free of concerns about solvent evaporation or deterioration of physical properties during handling and use. The viscosity of the epoxy resin composition of the present invention is important when producing a resin film with a release sheet using the hot melt method. The viscosity of the resin composition can be measured using a dynamic viscoelasticity analyzer, ARES-2KFRTN1-FCO-STD (manufactured by TA Instruments). Flat parallel plates with a diameter of 40 mm are used as upper and lower measuring jigs. The epoxy resin composition of the present invention is placed between the upper and lower jigs so that the distance between the upper and lower jigs is 1 mm, and the viscosity is measured at 70°C in torsional mode (measurement frequency: 0.5 Hz). In this case, a viscosity at 70°C of preferably 30 to 500 Pa·s, more preferably 200 to 500 Pa·s, ensures good processability. A viscosity of 30 Pa·s or more at 70°C is preferred because the resin film can stay on the release sheet without flowing, and a viscosity of 500 Pa·s or less at 70°C is preferred because a resin film with no defects and a stable basis weight can be produced on the release sheet.

[0050] The coating agent and resin film made of the epoxy resin composition of the present invention are effective when applied to or attached to a fiber-reinforced composite material precursor and then thermally cured together.

[0051] For ease of handling of the epoxy resin composition of the present invention, the epoxy resin composition of the present invention may be impregnated into a support such as a thermoplastic resin film, a fiber substrate, a metal foil, or a metal mesh, and then attached to an object in the form of an integrated surface protection intermediate substrate.

[0052] The surface protection intermediate substrate of the present invention can be produced by impregnating or attaching a resin film made from the epoxy resin composition of the present invention to a support. Impregnation may be performed from one side or both sides of the support. The degree of impregnation can be controlled by optionally applying pressure and heat during impregnation. Similarly, attachment may be performed from one side or both sides of the support, and the degree of attachment can be controlled by optionally applying pressure and heat. Furthermore, when the epoxy resin composition of the present invention is used as a coating agent, it can be applied to one or both sides of a support to form a surface protection intermediate substrate.

[0053] For good handling, it is preferable to impregnate one side of the support with the resin film or coat one side of the support with the coating agent so that a difference in tack is created between the two sides. By impregnating or coating one side, a difference in tack is created between the two sides of the surface-protecting intermediate substrate, so that the epoxy resin composition is less likely to adhere to hands on the side with low tack, and the side with high tack easily sticks to the object to be attached, making it possible to exhibit good adhesion to the object.

[0054] More preferred is a surface protection intermediate substrate in which a support is integrated with a resin film that has a higher viscosity, less fluidity, and higher tack than a coating agent by being impregnated with the support.

[0055] Preferred supports for the surface-protective intermediate substrate made from the epoxy resin composition of the present invention include polyimide films, PET films, and various carbon fibers, graphite fibers, glass fibers, PET fibers, nylon fibers, and aramid fibers and their substrates. The form of the fiber substrate is not particularly limited, and examples include unidirectionally aligned long fibers, tow, woven fabrics, mats, knits, braids, braids, and nonwoven fabrics. Metal foils and metal meshes can also be used as supports. Using metal mesh or metal foil as a support makes it possible to impart conductivity to the material, which is preferable. Using metal foil as a support is particularly preferable because it provides the aforementioned resin suppression effect. A surface-protective intermediate substrate can be produced by pre-curing a resin film and then integrating it with the support, for example by impregnation, or by pre-curing the integrated surface-protective intermediate substrate. Pre-curing of the resin film or surface-protective intermediate substrate is performed by heating. Heating may be performed using an oven, an IR heater, or by contacting the release paper surface of the resin film with a hot plate, among other methods. The temperature of the oven, furnace, IR heater, or hot plate during pre-curing is preferably 40 to 200°C. A temperature of 40°C or higher can shorten the pre-curing time, while a temperature of 200°C or lower can uniformly pre-cure the resin film or surface-protecting intermediate base material. In pre-curing by heating, the epoxy resin composition contained in the surface-protecting intermediate base material may be cured to the point where it loses its fluidity, or the degree of curing may be adjusted as desired to retain a certain degree of fluidity.

[0056] It is also preferable to prepare a surface-protecting intermediate substrate by integrating the epoxy resin composition of the present invention with the surface of a metal support such as a metal foil or metal mesh, and then integrating the epoxy resin composition with a fiber substrate such as a nonwoven fabric or woven fabric on the side opposite to the side integrated with the metal support. By using two types of supports, such a surface-protecting intermediate substrate increases the area over which the support supports the epoxy resin composition, preventing breakage and defects in the surface-protecting intermediate substrate, improving handleability, and further enhancing the effect of suppressing the mixing of the resins. It is also possible to impart electrical conductivity to the surface-protecting intermediate substrate.

[0057] The surface of the surface-protected intermediate substrate of the present invention to be placed on the surface of the fiber-reinforced composite material precursor can be selected depending on the structure and properties of the target fiber-reinforced composite material.

[0058] The width of the surface protection intermediate substrate of the present invention is not particularly limited, and a wide sheet of more than 1 m may be manually attached to the target surface, or a tape of 1 inch or less in width may be attached to the target surface using an automatic laminating device.

[0059] The weight of the support is 5 to 200 g / m 2 When the weight of the support is 5 g / m, the resin film becomes easy to handle. 2 If the thickness is more than 200g / m, the support will not tear easily when handled. 2 A thickness of not more than 1000 nm is preferable in that the resin film has good shaping properties.

[0060] The resin film made of the epoxy resin composition of the present invention has a basis weight of 10 to 300 g / m 2 It is preferable that the weight of the resin film is 10 g / m 2 When the weight of the resin film is 300 g / m or more, the support can be sufficiently impregnated, the mechanical properties such as the compressive and tensile properties of the surface protection intermediate substrate can be fully exhibited, and the blending of the above-mentioned resins can prevent the constituent resin of the surface protection target, which does not have UV resistance, from being exposed to the surface, which is preferable. 2 A thickness of 0.05 mm or less is preferable because heat generation due to curing of the epoxy resin composition of the present invention is suppressed and the drapeability of the resin film or surface protection intermediate substrate tends to be good. Drapability refers to flexibility in deformation and is a property that affects the ability to form onto a mold during lamination. If the drapeability is low, it is difficult to form onto a curved surface, and if the drapeability is too high, wrinkles are likely to form.

[0061] A resin film made from the epoxy resin composition of the present invention can be impregnated into reinforcing fibers such as carbon fiber, glass fiber, PET fiber, nylon fiber, and aramid fiber to form a fiber-reinforced composite material precursor. Among these, carbon fiber is preferred, as it produces a lightweight and highly rigid fiber-reinforced composite material. A preferred method for molding a fiber-reinforced composite material using a spray or hand-applied coating agent and resin film made from the epoxy resin composition of the present invention and a surface-protecting intermediate substrate is to apply or attach them to the outermost surface of the fiber-reinforced composite material precursor and then cure them together. The coating agent or resin film made from the epoxy resin composition of the present invention and the surface-protecting intermediate substrate are applied or attached to the outermost surface of the fiber-reinforced composite material precursor in a predetermined form, and then pressurized and heated to cure the coating agent or resin film made from the epoxy resin composition of the present invention, the surface-protecting intermediate substrate, and the resin contained in the fiber-reinforced composite material precursor, thereby producing a fiber-reinforced composite material. Examples of methods for applying heat and pressure include press molding, autoclave molding, bagging molding, wrapping tape molding, and internal pressure molding.

[0062] After pre-curing a fiber-reinforced composite material precursor by heating to adjust the degree of cure, the coating agent, resin film, and surface-protecting intermediate substrate according to the present invention are applied or attached to the surface of the fiber-reinforced composite material precursor to produce a fiber-reinforced composite material intermediate, which is then molded to produce a fiber-reinforced composite material. This suppresses the mixing of the resins described above. Suppressing the mixing of the resins is advantageous because it improves the UV resistance of the surface of the molded fiber-reinforced composite material. Various methods can be used to adjust the degree of cure of the fiber-reinforced composite material precursor. When using prepregs, for example, press molding, autoclave molding, bagging, tape wrapping, internal pressure molding, and pultrusion molding can be used to mold the material under heat and pressure. Various known methods can also be used to adjust the degree of cure of RTM materials. Methods such as VaRTM, in which resin is injected under vacuum pressure to suit the properties of the thermosetting resin used in the RTM material, and HP-RTM, in which resin is injected under high pressure, are used. The degree of cure is controlled by the temperature and time of pretreatment. When controlling the degree of cure, using a multi-stage process in which the curing temperature is changed in stages allows for more stable control of the degree of cure and is preferable from the perspective of reducing voids in the fiber-reinforced composite material. The degree of cure of RTM materials can also be controlled by heating them in an oven after demolding. A degree of cure of the fiber-reinforced composite material precursor of 30 to 70% is preferred because it increases the adhesion between the coating agent in the fiber-reinforced composite material and the fiber-reinforced composite material precursor, and a degree of cure of 80 to 100% is preferred because it reduces the likelihood of distortion during post-curing.

[0063] Roughening the surface of a fiber-reinforced composite precursor whose degree of cure has been adjusted by pre-curing by polishing or plasma treatment can improve adhesion between a spray- or hand-applied coating agent and resin film made from the epoxy resin composition of the present invention, a surface-protecting intermediate substrate, and the fiber-reinforced composite precursor, as well as adhesion between a spray- or hand-applied coating agent and resin film made from the epoxy resin composition of the present invention, a surface-protecting intermediate substrate, and the fiber-reinforced composite precursor in a fiber-reinforced composite material. Furthermore, roughening the surface of a molded fiber-reinforced composite material by polishing or plasma treatment can improve adhesion between a spray- or hand-applied coating agent and resin film made from the epoxy resin composition of the present invention, a surface-protecting intermediate substrate, and a paint or primer covering the surface. [Example]

[0064] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to these examples. Measurements of various properties were carried out in an environment of 23°C and 50% relative humidity unless otherwise noted.

[0065] <Materials used in Examples and Comparative Examples> (1) Aromatic epoxy resin Bisphenol A epoxy resin ("jER (registered trademark)" 828, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 175 (g / eq.).

[0066] (2) Component [A] Non-aromatic epoxy resin (3',4'-epoxycyclohexane) methyl 3,4-epoxycyclohexanecarboxylate (Celloxide® 2021P, manufactured by Daicel Corporation) Epoxy equivalent: 136 (g / eq.) 2,2-bis(hydroxymethyl)-1-butanol to 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct ("EHPE3150", Daicel Corporation) Diglycidyl ether of 2,2-bis(4-hydroxycyclohexyl)propane (YX8000, manufactured by Mitsubishi Chemical Corporation).

[0067] (3) Component [B] Pigment Titanium oxide (rutile type) (“Ti-Pure (registered trademark)” R-960, manufactured by Chemours, average particle size 0.5 μm).

[0068] (4) Component [C] Non-aromatic thermoplastic resin Polyvinyl formal ("Vinylec (registered trademark)" K, manufactured by JNC Corporation, calculated molecular weight 40,000 to 54,000 g / mol) Polyvinyl acetoacetal ("S-LEC (registered trademark)" KS-10, manufactured by Sekisui Chemical Co., Ltd., calculated molecular weight 17,000 g / mol).

[0069] (5) Component [D] Non-aromatic acid anhydride Hexahydrophthalic anhydride (Rikacid (registered trademark) HH, manufactured by Shin-Nihon Rikagaku Co., Ltd.) A mixture of methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride and bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride ("Rikacid (registered trademark)" HNA-100, manufactured by Shin-Nihon Rikagaku Co., Ltd.) (6) Component [E] Curing accelerator Triphenylphosphine (Hokko Chemical Industry Co., Ltd.) 1,2-Dimethylimidazole ("Curezol" 1,2DMZ, manufactured by Shikoku Chemical Industries, Ltd.) (7) Component [F] Thixotropy-imparting agent Fumed silica ("AEROSIL (registered trademark)" RY200S, manufactured by Nippon Aerosil Co., Ltd.).

[0070] (8) Metal foil ·Pure copper (C1020-R, manufactured by Takeuchi Metal Foil and Powder Industry Co., Ltd.).

[0071] <Methods for producing and evaluating epoxy resin compositions and fiber-reinforced composite materials> The epoxy resin compositions of the examples and comparative examples were measured by the following methods.

[0072] (1) Preparation of epoxy resin composition An epoxy resin corresponding to component [A] listed in Tables 1 to 3 (including the aromatic epoxy resin in Comparative Example 1), a pigment corresponding to component [B], and a thixotropy-imparting agent [F] as listed in the table were charged into a three-roll mill and mixed to obtain a powder mixture precursor. The powder mixture precursor and a non-aromatic thermoplastic resin corresponding to component [C] listed in Tables 1 to 3 were charged into a mixer and heated and mixed to dissolve the non-aromatic thermoplastic resin. Next, while continuing to knead, the temperature was lowered to 60°C or below, and a non-aromatic acid anhydride [D] listed in Tables 1 to 3 and, except for Comparative Example 2, a curing accelerator [E] were added and stirred to obtain an epoxy resin composition.

[0073] (2) Resin film manufacturing method The epoxy resin composition prepared by the method (1) above was applied to a knife coater at a rate of 100 g / m 2 The resin was applied to a release paper at a resin basis weight of 100g to produce a resin film. The quality of the produced resin film was also visually confirmed. Poor quality may be due to areas on the release paper where the resin was not applied in streaks or dots, areas where the resin was applied in islands, the resin film basis weight being 10% or more off the target resin basis weight, or the resin not passing through a knife coater. A resin film of good quality is one in which the above problems are not present.

[0074] (3) Method for producing surface protection intermediate substrate Surface protection intermediate substrates were obtained by impregnating one side of a glass fabric (E01Z 4W 106KH, manufactured by Unitika Ltd.) with the resin film prepared in (2) above, or by attaching the resin film prepared in (2) above to one side of a metal foil (C1020-R, manufactured by Takeuchi Metal Foil & Powder Co., Ltd.). The impregnation or attachment method involved sandwiching the resin film with the glass fabric or metal foil attached between release papers on both sides and evacuating for 1 minute.

[0075] (4) Viscosity measurement of epoxy resin composition at 70°C The viscosity of the epoxy resin composition prepared in (1) above at 70°C was measured using a dynamic viscoelasticity analyzer ARES-2KFRTN1-FCO-STD (manufactured by TA Instruments) with flat parallel plates 40 mm in diameter as the upper and lower measuring jigs, with the epoxy resin composition set so that the distance between the upper and lower jigs was 1 mm, in torsional mode (measurement frequency: 0.5 Hz) at an isothermal temperature of 70°C for 10 minutes. The average viscosity value from 2 to 10 minutes after the start of measurement was taken as the viscosity of the epoxy resin composition at 70°C.

[0076] (5) Pot life measurement of epoxy resin composition The viscosity of the epoxy resin composition prepared in (1) above was measured using a dynamic viscoelasticity analyzer ARES-2KFRTN1-FCO-STD (manufactured by TA Instruments) in torsion mode (measurement frequency: 0.5 Hz) with flat parallel plates of 40 mm diameter as the upper and lower measuring jigs, with the distance between the upper and lower jigs being 1 mm. The viscosity η after holding at 70°C for 2 minutes was * 2. Keep at 70°C for 2 hours, and measure the viscosity η at any time. * x The viscosity increase ratio at that time is η * x ÷η * The time required for the viscosity increase ratio to reach 3 was defined as the pot life.

[0077] (6) Measurement of volatilization amount of epoxy resin composition 3 g of the epoxy resin composition prepared in (1) above was weighed out (mass: W2) on release paper (mass: W1), and the epoxy resin composition thinly spread on the release paper was placed together with the release paper in an oven at 180°C for 1 hour. Thereafter, the epoxy resin composition and release paper were removed from the oven and left in a desiccator for 30 minutes, after which the combined mass of the epoxy resin and release paper was measured (mass: W3), and the volatilization amount [%] in the present invention was calculated using the following formula: {(W2-(W3-W1)} / W2×100[%] A calculated volatilization amount of 10% or less was rated as "good," and a calculated volatilization amount of more than 10% was rated as "poor."

[0078] (7) Resin flow measurement of epoxy resin composition The epoxy resin composition prepared in (1) above was weighed out to a target of 3 g onto a 15 cm square piece of release film (mass: W4). The epoxy resin composition was sandwiched between another 15 cm square piece of release film, and then sandwiched between two 10 cm square metal plates (400 g per plate). This state was molded in an autoclave (6 atmospheres, 180°C, 2 hours, temperature increase 1.7°C / min). After molding, the cured epoxy resin composition that protruded from the 10 cm square metal plates was removed, and the mass of the remaining cured epoxy resin composition was measured (mass: W5). The resin flow amount [%] of the epoxy resin composition of the present invention was calculated using the following formula: (W4-W5) / W4×100[%] Resin flow amount is designated as A if it is 5% or less, B if it is more than 5% and less than 10%, C if it is more than 10% and less than 15%, and D if it is more than 15%.

[0079] (8) UV irradiation test of epoxy resin composition The epoxy resin composition prepared in (1) above was applied to a release film to a thickness of 80 μm, and cured in an oven at 180°C for 2 hours with a temperature increase of 1.7°C / min. The surface of the cured epoxy resin composition obtained was half-covered with aluminum foil, and the cured epoxy resin composition was measured using a metaling weather meter (M6T, manufactured by Suga Test Instruments Co., Ltd.) at an irradiation wavelength of 300 to 400 nm and an integrated illuminance of 1.55 kW / m 2 Furthermore, since it is expected that the cured product of the epoxy resin composition of the present invention will be exposed to sunlight outdoors for years, the cumulative intensity is set to 1000 kJ / m, which is the approximate value of the amount of UV light in one month in Japan (summer). 2After irradiation, the aluminum foil was peeled off, and the appearance of the area covered with the aluminum foil and the area not covered with the foil was visually inspected to check for discoloration of the cured epoxy resin before and after UV irradiation. The color difference of the cured epoxy resin composition before and after irradiation was measured using a multi-light source spectrophotometer (MSC-P, manufactured by Suga Test Instruments Co., Ltd.). The epoxy resin composition was placed in the multi-light source spectrophotometer, and the reflectance was measured in the wavelength range of 380 to 780 nm under the following measurement conditions: reflection mode, C light source, 2° field of view, and 8° incident angle. Furthermore, using the program attached to the device, L * a * b * Color measurement value (L * 1a * 1b * Next, after UV irradiation (L * 2a * 2b * 2) was measured. Furthermore, the color difference ΔE of the cured product of the epoxy resin composition before and after UV irradiation was measured. * ab to ΔE * ab=[(L * 1-L * 2) 2 +(a * 1-a * 2) 2 +(b * 1-b * 2) 2 ] 1 / 2 The calculated ΔE * If ab is 4 or less, the UV resistance is considered to be "good (no discoloration)" and ΔE * If ab exceeded 4, the UV resistance was rated as "poor (discoloration present)."

[0080] (9) Amount of prepreg resin mixed (incorporated) into the material consisting of the epoxy resin composition during the molding process Eight layers of continuous fiber prepreg (T800S / 3900-2B (Toray Industries, Inc.)) were laminated to create a quasi-isotropic structure (lamination configuration: [+45° / 0° / -45° / 90°]). sOn the outermost surface of the substrate, a coating agent consisting of the epoxy resin composition prepared in (1) above was applied or the surface-protected intermediate substrate prepared in (3) above was attached so that the epoxy resin composition had a thickness of 80 μm. Then, in this state, molding was performed in an autoclave under conditions of 6 atmospheres, 180°C for 2 hours, and a temperature increase of 1.7°C / min. The surface of the surface-protected intermediate substrate attached to the fiber-reinforced composite precursor was the resin film side when the support was glass fabric or metal foil, and the glass fabric side when both glass fabric and metal foil were used as supports. The cured side of the epoxy resin composition of the resulting composite material was measured by IR measurement using the ATR method (FT / IR-4000, manufactured by JASCO Corporation, prism: diamond, measurement wavelength: 400 to 4000 cm). -1 , accumulation number: 16 times) and the ester is shown at 1715 cm -1 The peak at 1592 cm indicates the benzene ring originating from the cured resin used in the prepreg. -1 The peak value of this peak was evaluated. The amount of resin used in the prepreg that was mixed with the coating agent or surface protective intermediate substrate made of an epoxy resin composition during the molding process and exposed to the surface of the fiber-reinforced composite material can be determined by evaluating this peak value. If the peak value was 0.7 or less, the UV resistance of the surface of the fiber-reinforced composite material was judged to be good.

[0081] (10) Method for protecting prepreg surface with epoxy resin composition When applying by spraying, the epoxy resin composition was sprayed onto the surface of the prepreg using a spray gun W-2001-2 (manufactured by Anest Iwata Corporation).

[0082] When applying by hand, the epoxy resin composition was placed on the surface to be coated and spread with a bar coater to coat the surface, or the surface protection intermediate substrate prepared in (3) above was attached to the surface of the object.

[0083] (11) Method for measuring exothermic peak temperature of epoxy resin composition An exothermic curve of the epoxy resin composition was obtained using a differential scanning calorimeter (DSC Q2500, manufactured by TA Instruments) at a heating rate of 5°C / min in a nitrogen atmosphere. The temperature at the apex of the exothermic peak where the calorific value was 100 mW / g or more in the obtained exothermic curve was calculated as the exothermic peak temperature. When there were two or more exothermic peaks where the calorific value was 100 mW / g or more, the temperature at the apex of the peak on the lower temperature side was calculated as the DSC exothermic peak temperature in the present invention. Regarding the evaluation of low-temperature curability, in Tables 1 to 3, an exothermic peak temperature of 100°C or less was represented by A, a peak temperature of more than 100°C and 120°C or less was represented by B, a peak temperature of more than 120°C and 140°C or less was represented by C, and a peak temperature of more than 140°C was represented by D.

[0084] <Examples 1 to 20 and Comparative Examples 1 to 5> In Examples 1 to 20 and Comparative Examples 2 to 5, epoxy resin compositions were prepared using the non-aromatic epoxy resins described in (1) above as component [A], either alone or in combination as shown in Table 1. In the UV resistance test, no discoloration was observed even after curing, and good results were obtained. On the other hand, in Comparative Example 1, which did not contain the non-aromatic epoxy resin as component [A] and contained only an aromatic epoxy resin, the UV resistance test was judged to be poor, indicating low UV resistance.

[0085] <Examples 1 to 2, 5, 7, 11, and 12, and Comparative Example 4> In each of Examples 1 and 2 (application method: spraying) and Examples 5 and 7 (application method: hand application using a bar coater), the type of component [C] was changed and the amount added was adjusted to achieve the same viscosity at 70°C. The results showed that the use of polyvinyl acetoacetal compared to polyvinyl formal resulted in a greater effect of suppressing the amount of resin flow (7). In Examples 11 and 12 (where the surface protection method was the attachment of a surface-protected intermediate substrate), the type of component [C] was changed and the blending amount was the same at 50 parts by mass. As a result, it was shown that the viscosity at 70°C was lower when polyvinyl acetoacetal was used compared to polyvinyl formal.

[0086] On the other hand, in Comparative Example 4, when the component [C] was not included, the amount of resin flow in (7) was large, and the amount of resin in the prepreg mixed in the molding process described in (9) was excessive, and the product was judged to be defective.

[0087] <Examples 1 and 3, Comparative Example 2> The type of component [E] was changed in Examples 1 and 3. The compound containing 1,2-dimethylimidazole compared to triphenylphosphine exhibited a lower exothermic peak temperature and better low-temperature curing properties.

[0088] On the other hand, when component [E] was not blended as in Comparative Example 2, the exothermic peak temperature was high, the amount of resin flow after autoclave molding in (7) was large, and the amount of resin in the prepreg mixed in the molding process described in (9) was excessive, resulting in a judgment of failure. In addition, the amount of volatilization was also excessive, resulting in a judgment of failure.

[0089] <Examples 1, 4, 5 to 8, 11, 14 to 17> In Examples 4, 6, and 14, the type of component [A] was changed to a diglycidyl ether of 2,2-bis(4-hydroxycyclohexyl)propane, respectively, compared to Examples 1, 5, and 11. In Example 6, the non-aromatic thermoplastic resin was further changed from that in Example 5. In Examples 4, 6, and 14, the exothermic peak temperature was higher than in the respective Examples before the change, while the pot life was improved.

[0090] In Examples 8 and 15, the type of component [A] was changed to a 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol in each of Examples 5 and 11. In Examples 8 and 15, the exothermic peak temperature was higher than in the respective Examples before the change, but the pot life was improved.

[0091] Two types of component [A] were blended in Examples 7, 16, and 17. Compared with Examples containing only one type of component [A], it was shown that the balance between low-temperature curing properties and pot life was better.

[0092] <Examples 3, 9, 11, and 18> In Examples 9 and 11, the type of component [D] was changed to a mixture of methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride and bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, as compared to Example 3. Furthermore, the non-aromatic thermoplastic resin was changed as shown in the table. It was shown that Examples 9 and 11 had higher exothermic peak temperatures than Example 3 before the change.

[0093] Two types of component [D] were blended in Example 18. Compared with examples containing only one type of component [D], it was shown that the balance between low-temperature curing properties and pot life was good.

[0094] <Examples 9, 10, 11, and 19, and Comparative Example 5> In Examples 10 and 19, the amount of component [F] was increased from that in Examples 9 and 11, respectively. As the amount of component [F] increased, the viscosity at 70°C improved, and it was shown that the amount of resin flow after autoclave molding (7) and the amount of resin in the prepreg mixed in the molding process described in (9) were suppressed.

[0095] On the other hand, in Comparative Example 5, which did not contain the component [F], the amount of resin flow after autoclave molding in (7) was large, and the amount of resin in the prepreg mixed during the molding process was excessive, so it was judged to be defective.

[0096] <Examples 11 and 13> In Example 13, the amount of component [C] was increased from that in Example 11. As the amount of component [C] increased, the viscosity at 70°C improved, and it was shown that the amount of resin flow after autoclave molding (7) and the amount of resin in the prepreg mixed during the molding process described in (9) were suppressed.

[0097] <Examples 11 and 20, Comparative Example 3> In Example 20, the amount of component [B] was increased from that in Example 11. As the amount of component [B] increased, the viscosity at 70°C improved, and it was shown that the amount of resin flow after autoclave molding (7) and the amount of resin in the prepreg mixed during the molding process were suppressed.

[0098] On the other hand, in Comparative Example 3, which did not contain component [B], the amount of resin mixed into the prepreg during the molding process was excessive, and the material was judged to be defective. Furthermore, in the obtained fiber-reinforced composite material, the cured surface-protecting intermediate substrate of Comparative Example 3 was visible, allowing direct light irradiation of the substrate.

[0099] Examples 21 to 31 and Comparative Examples 6 to 8 In each of Examples 21 to 30, a resin film made from the epoxy resin composition described in each of Examples 11 to 20 was attached to a metal foil (C1020-R, manufactured by Takeuchi Metal Foil & Powder Co., Ltd.) to prepare a surface-protecting intermediate substrate. In Example 31, a glass fabric (E01Z 4W 106KH, manufactured by Unitika Ltd.) was laminated to one side (the resin film side) of the surface-protecting intermediate substrate of Example 30, and the glass fabric was impregnated with the resin composition contained in the intermediate substrate to prepare a surface-protecting intermediate substrate. Using these surface-protecting intermediate substrates, the amount of resin in the prepreg to be mixed during the molding process was measured.

[0100] In comparison with Examples 11 to 20, Examples 21 to 30, which used a surface-protecting intermediate base material with a metal foil support, showed that the amount of resin in the prepreg mixed during the molding process was suppressed.

[0101] In comparison with Example 30, Example 31 showed that the amount of resin in the prepreg mixed during the molding process was suppressed.

[0102] In each of Comparative Examples 6 to 8, a surface-protecting intermediate substrate was prepared by attaching a resin film made from the epoxy resin composition described in each of Comparative Examples 1 to 3 to a metal foil (C1020-R, manufactured by Takeuchi Metal Foil & Powder Co., Ltd.) The amount of resin in the prepreg mixed during the molding process was measured using the surface-protecting intermediate substrate.

[0103] In Comparative Examples 6 to 8, as in Comparative Examples 1 to 3, the amount of resin in the prepreg mixed in the molding process described in (9) was excessive, and the products were judged to be defective.

[0104] [Table 1]

[0105] [Table 2]

[0106] [Table 3]

[0107] [Table 4]

[0108] [Table 5]

Claims

1. An epoxy resin composition comprising the following amounts of components [A] to [F] per 100 parts by mass of the total epoxy resin: [A] Non-aromatic epoxy resin 90 to 100 parts by mass [B] Pigment having an average particle size of 0.1 to 10 μm: 0.05 to 75 parts by mass [C] Non-aromatic thermoplastic resin 0.05 to 100 parts by mass [D] Non-aromatic acid anhydride 50 to 200 parts by mass [E] Curing accelerator 0.1 to 10 parts by mass [F] Thixotropic agent: 0.1 to 20 parts by mass

2. The epoxy resin composition according to claim 1, comprising 0.05 to 30 parts by mass of a non-aromatic thermoplastic resin [C] relative to 100 parts by mass of the total epoxy resins.

3. 3. The epoxy resin composition according to claim 1, having a viscosity at 70° C. of 0.01 to 30 Pa·s.

4. The epoxy resin composition according to claim 1, comprising 30 to 100 parts by mass of the non-aromatic thermoplastic resin [C] relative to 100 parts by mass of the total epoxy resins.

5. 5. The epoxy resin composition according to claim 1, having a viscosity at 70° C. of 30 to 500 Pa·s.

6. 6. The epoxy resin composition according to claim 1, wherein the non-aromatic compound is contained in an amount of 90 mass% or more based on the total epoxy resin.

7. The epoxy resin composition according to any one of claims 1 to 6, wherein the epoxy resin composition further comprises a component [G] rubber.

8. The epoxy resin composition according to any one of claims 1 to 7, wherein the epoxy resin composition comprises at least two kinds of non-aromatic epoxy resins as component [A].

9. The epoxy resin composition according to any one of claims 1 to 8, wherein the non-aromatic thermoplastic resin as component [C] is at least one selected from the group consisting of polyvinyl alcohol, polyvinyl formal, polyvinyl butyral, polyvinyl acetoacetal, and polyvinyl acetate.

10. The epoxy resin composition according to any one of claims 1 to 9, wherein the DSC exothermic peak temperature is 80 to 120°C.

11. The epoxy resin composition according to any one of claims 1 to 10, which has an amount of volatilization of 10% or less after being placed in an environment of 180°C for 1 hour.

12. The cured product of the epoxy resin composition is exposed to ultraviolet light of 300 to 400 nm in wavelength at 1000 kJ / m 2 The epoxy resin composition according to any one of claims 1 to 11, wherein the formula difference ΔE*ab after irradiation is 4 or less.

13. An epoxy resin composition as described in claim 1 for use in applying or attaching to the surface of a fiber-reinforced composite material precursor and thermally curing both.

14. A surface protection intermediate substrate comprising the epoxy resin composition according to any one of claims 1 to 13 integrated with reinforcing fibers.

15. A surface protection intermediate substrate comprising a metal mesh or metal foil and the epoxy resin composition according to any one of claims 1 to 13 integrated onto the surface thereof.

16. 16. The surface protection intermediate substrate according to claim 15, wherein a nonwoven fabric or woven fabric is integrated on the surface of the epoxy resin composition opposite to the surface on which the metal mesh or metal foil is integrated.

17. A fiber-reinforced composite material intermediate, comprising: an epoxy resin composition according to any one of claims 1 to 13 applied to a surface of a fiber-reinforced composite material precursor; or a surface-protecting intermediate base material according to any one of claims 14 to 16 disposed on the surface of a fiber-reinforced composite material precursor.